The existence and approximation of the periodic solutions for system of second order nonlinear differential equationsby using Lebesgue integrable - Merna Adel Aziz; R.N. Butris (College of Education for Pure Sciences, 2007)
ABSTRACT In this paper we study the existence and approximation of the periodicsolutions for system of second order nonlinear differential equations according to Lebesgue integrable concept and by assuming that each of measurable at t and bounded by the functions Lebesgue integrable functions numerical -- analytic method has been used to study the periodic The solutions of ordinary differential equations which were introduced by A.M. Samoilenko.